« Et que fais-tu de cinq cents millions d’étoiles ? » - Samuel Challéat; Thomas Poméon (Ateliers d'Anthropologie)
If “that which is rare is precious”, then that which becomes scarce gains value. More precisely—and because nothing is created ex nihilo—the value of that thing, previously little-known or neglected, ends up being revealed by the threat of its erosion. Under the effect of light pollution, darkness and the starry sky are among those objects that have become rare, and we are assessing what they provide now that they seem to be eluding us. In reaction to this, territories are organising the protection of these “objects of nature” that have become precious, thus activating their multiple values. Feet on the ground and head in the stars, we look at values that are emerging from the starry sky industry and from the multiple services and activities it valorises, not only monetarily. Being in tension with other human needs and activities, access to darkness and therefore to the starry sky is more and more unequally distributed in space. Nevertheless, for territories previously isolated from the gains of modernity, this spatial disparity is turning into a new card to play.